Ergonomic risk evaluation to minimize musculoskeletal disorders of workers at batik cap industry - Indah Pratiwi; Hernanning Wahyu Nuriati (Jurnal Sistem dan Manajemen Industri, 2022)
This research was carried out in Batik Cap production in Surakarta, Indonesia. Creating and producing batik is still done manually with non-ergonomic work postures and repetitive movements that can cause musculoskeletal disorders (MSDs). The study aimed to determine the risk level of injury of MSDs in the work posture that focuses on the upper body and analyze the risk factors of muscle injury with different upper body regions. Data collection used five workstations with 22 activities for Batik Cap workers. Data analysis used the Plan for Identifiering av. Belastningsfaktorer (PLIBEL) checklist and the Quick Exposure Checklist (QEC) method. The results of the PLIBEL checklist show six activities included in the fair category, 14 in the moderate category, and two in the substantial category. The QEC method results show 20 activities in the action level 3 category, which means further investigated and changes are needed. Two activities in category 4 mean that investigation and change need to be done as soon as possible. In conclusion, the result shows that redesigning and designing work facilities is expected to reduce workers’ muscle injury risk, especially in the back, neck, elbow, forearm, and hands which can cause MSDs.